Preparation, Characterisation and Adsorption properties of graphene-oxide@Ni-Al layered double hydroxide composites - (:unkn) unknown (My University, 2023)
In order to treat wastewater and remove toxins from industrial wastewater, GO modified Ni-Al Layered double hydroxide with different weight % was synthesized by varying the amount of GO from 1 to 5 wt % onto a fixed amount of Ni-Al LDH by co-precipitation method. The composites were abbreviated as GO(x)@LDH, where x= 1, 3, 5 wt %. The as synthesized catalysts Ni-Al LDH, GO, GO(x)@LDH were characterized using XRD, FTIR, FESEM, EDS, Raman and DRS techniques. The GO(5)@LDH catalyst proved to be the best catalyst for the removal of ciprofloxacin drug . The catalyst removed the pollutant by 87.4% in 180 min. The composites of LDH with GO had greater surface area (SBET) than the bare LDH, which was found to be 3.5456 m2/g, 19.575 m2/g and 22.5591 m2/g for Ni-Al LDH, GO(1)@LDH and GO(5)@LDH respectively. From Langmuir adsorption isotherm the adsorption capacity (qmax) for GO(5)@LDH was 1968.5 mg/g. The as synthesized catalysts follows both Langmuir and Freundlich adsorption isotherms. The possible adsorption mechanism has been shown. The kinetic study shows that the pseudo second order kinetics has been followed. The catalyst has been used successfully for four repeating cycles with only 10% decrease in the removal rate. The stability for the GO(5)@LDH composite was checked by comparing the before and after XRD patterns.
Keywords: Graphene Oxide; Layered double hydroxide; adsorption; waste water treatment; reusability